Selected Forms Of Rehabilitation In Nursing Homes - Rynkowska, Dorota (European Scientific Journal, ESJ, 2016)
Elderly, often disabled people, who live in nursing homes require psychotherapeutic and rehabilitative activities adopted to their condition of health. All activities undertaken with the aim to improve physical and mental health of residents are of paramount importance. The forms of rehabilitation applied in nursing homes are multidisciplinary and they are based on potential for development which is deeply rooted in every man, whether old or sick. This potential has its source in natural vitality of every man, regardless of the level of disability. Various methods of rehabilitation allow residents to free their abilities and predispositions, which makes it possible for them to take part in everyday life of a nursing home community. The main aim of rehabilitation is the improvement of physical and mental health of every person or group of people living in the institution.